Studi Penerapan Modifikasi Algoritma Flood fill Pada Multi-AgenUntuk Mencari Jalan tercepat Dalam Labirin - Tjiharjadi, Semuil (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
This research is structured to serve as an essential foundation for the development of automated pathfinding systems using Multi-Agent Pathfinding (MAPF) methods within maze environments. Although the Flood fill algorithm has long been recognized and widely used for maze solving by single agents, its application in multi-agent configurations remains limited and requires adaptive innovation. Therefore, this study reviews various related research on MAPF and relevant maze algorithms, proposing modifications to the Flood fill algorithm to enable effective operation in multi-agent scenarios. By expanding the capacity of Flood fill, it is anticipated that the algorithm's advantages, such as low complexity and fast execution, can be harnessed in dynamic multi-agent systems. The primary contribution of this research highlights the significance of implementing a modified Flood fill algorithm as an innovative basis for pathfinding solutions involving multiple agents simultaneously, thereby opening opportunities for more efficient and adaptive robotic and automation system developments